James Matthews: The Stories Behind The Dissident Poet - Naidoo, Kareesha; Singh, Nehna (WritingThreeSixty: Journal or Research and Creative Text, 2018)
WritingThreeSixty met with renowned poet, James Matthews, on Thursday, 6 August 2015, to discuss hismost recent publication, his past collections of poetry, as well as his time spent in prison.